Development of Rotating Wheel Teaching Aids for Volume and Surface Area of ​​Flat-Sided Solid Geometry for Grade IX MTs Tarbiyatul Islamiyah - Raifatul Maghfiroh; Arini Hidayati (Global Education Journal, 2026)
Mathematics learning, particularly on the topic of volume and surface area of polyhedrons, remains challenging due to students' limited conceptual understanding and the lack of concrete instructional media. This study aimed to develop a rotating wheel teaching aid that meets the criteria of validity, practicality, Universitas Nurul Jadid, Indonesia and effectiveness for Grade IX students at MTs Tarbiyatul Islamiyah. The study employed a Research and Development (R&D) approach using the Four-D (4D) model, consisting of the Define, Design, Develop, and Disseminate stages. The product was tested on 10 ninth-grade students. Data were collected through validation sheets, student response questionnaires, and learning achievement tests, and were analyzed using descriptive quantitative and qualitative methods. The results showed that the developed teaching aid achieved a validation score of 4.02 (very valid), while the student response questionnaire and achievement test obtained validation scores of 3.05 and 3.02, respectively (valid). The practicality of the media was indicated by an average student response score of 3.56 (high), whereas its effectiveness was demonstrated by an average learning achievement score of 9 4 with a classical learning mastery of 80% (8 out of 10 students). Therefore, the rotating wheel teaching aid is considered valid, practical, and effective for teaching the volume and surface area of polyhedrons.